CONSUMER PROTECTION AS A KEY ASPECT OF UKRAINE’S SOCIO-ECONOMIC DEVELOPMENT - VASIUTA, Viktoriia; YEMETS, Viacheslav; MALENKO, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the key aspects of consumer protection as an important component of the socio-economic development of the state. The historical stages of the formation of the consumer protection system in the world and in Ukraine, starting from medieval norms and ending with modern international initiatives, in particular the UN Guidelines on Consumer Protection OF THE UNITED NATIONS. Particular attention is paid to the current state of consumer protection in Ukraine, including legal reforms and the application of international experience. The author identifies the main problems in this area: violation of requirements for the quality of goods and services, lack of reliable information about products, sale of dangerous or expired products. The mechanisms for ensuring consumer rights, including legislative innovations, e-commerce, information support and mechanisms for resolving consumer disputes, are considered. International practice in this area provides important recommendations and standards that contribute to the improvement of legislation and practical measures to protect the interests of consumers. Ukraine, like many other countries, is actively applying international experience to improve national regulations and enhance the effectiveness of protecting the rights of its citizens. The article emphasizes the importance of improving legal regulation, expanding product quality control and coordination between government agencies, NGOs and consumers. The author highlights the prospects for implementing international practices to raise consumer protection standards and improve the quality of life of citizens. The author emphasizes the importance of introducing international experience into national practice to build an effective consumer protection system, as well as the challenges associated with violations of citizens’ rights and the lack of information support.